Effect of School Welfare on English Teachers’ Job Satisfaction in the Selected Secondary Schools in Kabale Municipality. - Tukamusiima, Carolyne (Kabale University, 2024)
The study investigated the impact of school welfare on job satisfaction among English teachers in selected secondary schools in Kabale Municipality. The objectives included assessing how housing conditions affect job satisfaction, examining the contribution of meal provision to job satisfaction, and determining the effect of medical care provision on job satisfaction among English teachers in these schools. A cross-sectional survey was employed, utilizing questionnaires and interviews for data collection. Findings indicated that adequate and affordable housing positively impacts English teachers' well-being, contributing to their job satisfaction. Good housing conditions close to the school enable teachers to have sufficient time to prepare lesson plans and teach effectively. Additionally, the study revealed that providing meals for English teachers leads to increased job satisfaction, as it saves time that would otherwise be spent seeking food outside the school. Nutritious meals also enhance teachers' overall well-being, further contributing to their job satisfaction. Furthermore, the study found that access to medical care fosters peace of mind among teachers, which in turn enhances job satisfaction. This provision allows teachers to address their health needs, promoting greater job satisfaction overall. The study recommends that educational associations and teacher unions advocate for housing support and policies that promote work-life balance at both regional and national levels to ensure English teachers' job satisfaction. It also suggests implementing wellness programs focused on healthy lifestyles, including exercise, nutrition, and stress management, to improve care for teachers.